METHODS OF INFORMATION PROTECTION (Conferencea, 2021)
Information today is an important resource, the loss of which is fraught with unpleasant consequences. The loss of confidential company data carries the threat of financial losses, since the information obtained can be used by competitors or attackers. To prevent such undesirable situations, all modern firms and institutions use information protection methods. Information Systems Security (IS) is a whole course that all programmers and specialists in the field of building IS take. However, it is necessary to know the types of information threats and protection technologies for everyone who works with secret data.